Presence of hydrocarbons and heavy metals in some fish species in the cross river, Nigeria. (2004)
The study was undertaken to determine the total hydrocarbon (THC) and heavy metal contents of fish (finfish and shelf fish) in the cross river, Nigeria. Fish samples were collected in the dry (March) and rainy (October) seasons between 2000-2002. The finfish species identified in the study were Synodontis clarias, Sarotherodon galilaeus, Heterotis niloticus, Scholbe mystus, ansorgil and the shelfish were macrobrachium vollenhovonii and tympanotnomus luscalus. Significant difference (P<0.05) existed between finfish andshellfish in both THC and heavy metals contents. The levels of THC in fish exceeded the World Health Organization's limit of 0.0001 ppm by an average of 3.2 and 15.57 mg/kg in fin and shelffish respectively. High concerntrations of vanadium and THC in fish samples were the main indicators of pollution from petroleum sources